2009
DOI: 10.1103/physrevlett.103.186801
|View full text |Cite
|
Sign up to set email alerts
|

Giant Surface-Plasmon-Induced Drag Effect in Metal Nanowires

Abstract: Here, for the first time we predict a giant surface-plasmon-induced drag-effect rectification (SPIDER), which exists under conditions of the extreme nanoplasmonic confinement. In nanowires, this giant SPIDER generates rectified THz potential differences up to 10 V and extremely strong electric fields up to approximately 10(5)-10(6) V/cm. The giant SPIDER is an ultrafast effect whose bandwidth for nanometric wires is approximately 20 THz. It opens up a new field of ultraintense THz nanooptics with wide potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 23 publications
1
51
0
Order By: Relevance
“…Although other possible enabling mechanisms of PDE, e.g. the ones associated with the Doppler effect [9] or the striction forces [16] cannot be excluded, at this point we do not have evidence of their significant roles.…”
Section: Discussion Of the Experimental Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Although other possible enabling mechanisms of PDE, e.g. the ones associated with the Doppler effect [9] or the striction forces [16] cannot be excluded, at this point we do not have evidence of their significant roles.…”
Section: Discussion Of the Experimental Resultsmentioning
confidence: 60%
“…Plasmon-induced enhancement of PDE was observed in thin gold films [15], where the phenomenon was explained by an increase of light absorption under resonant condition of surface plasmon polariton (SPP) excitation. The recent theoretical study [16] has predicted a much stronger plasmon-induced photon drag effect in thin metallic nanowires, which was not only due to increased optical fields inside nanowires but rather due to extremely high gradients of electric fields (striction forces).…”
Section: Introductionmentioning
confidence: 99%
“…In [7], it was shown that in plasmonic gratings with a smooth modulation profile and a relatively low modulation amplitude, photocurrents can be reasonably well described with the 'plasmonic pressure' mechanism [21,22]. In the current work we use plasmonic gratings with steep edges and a relatively high amplitude profile modulation, and observe quite unusual behavior of the photocurrents.…”
Section: Introductionmentioning
confidence: 82%
“…Possible mechanisms of the voltage generation in nanofeatures may include thermoelectric effects [39], nonlinearity and asymmetry of electron motion [3,40] or charging due to high field gradients, which can be described theoretically [21] in terms of the effective striction force. The striction force is conservative [22]; it is expected to affect only the electron density distribution and not result in the total photocurrent across the sample even in the case of a highly asymmetric intensity distribution around a nanofeature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hybridizing plasmonic structures with active photonic media may be another feasible approach to reducing or eliminating Ohmic loss by coherently amplifying the attenuated signals in plasmonic waveguides , as well as by minimizing the use of plasmonic nanowaveguides in the hybrid “photon‐plasmon” circuits or devices . Finally, beyond waveguiding optical‐frequency photons and electrons, a metal nanowire with subwavelength diameter is also possible to waveguide or manipulate many other energy forms such as phonons and atoms, as well as photons or electrons with oscillating frequencies spanning from UV to beyond THz , providing a versatile platform for combining waveguide optics, near‐field optics, optoelectronics, plasmonics, nonlinear optics, atom optics, optomechanics and quantum optics on a single nanowire, which may open new opportunities for photonic applications ranging from generation, transportation, modulation and detection of light for future photonic and plasmonic circuits and devices.…”
Section: Discussionmentioning
confidence: 99%